Drug‐induced pneumonitis risk in diffuse large B‐cell/follicular lymphoma patients treated with R‐CHOP‐like regimen is associated with the use of granulocyte colony‐stimulating growth factors - Elina Kaprio; Roosa Prusila; Susanna Tokola; Milla E. L. Kuusisto; Esa Jantunen; Hanne Kuitunen; Taina Turpeenniemi‐Hujanen; Outi Kuittinen (Cancer Medicine, 2024)
Abstract Background Rituximab‐based combinations are the standard of care in diffuse large B‐cell lymphoma (DLBCL) and follicular lymphoma (FL). Despite being on market for over 20 years, some of the adverse effects associated with the use of rituximab are not well known. Drug‐induced interstitial pneumonitis (DIP) is a potentially fatal complication of the treatment. Granulocyte colony‐stimulating factors (G‐CSF) are supportive agents commonly used to prevent neutropenic infections. G‐CSF are reported to have pulmonary toxicity, but the risk of DIP is greater when used in combination with other potentially pulmotoxic agents. Methods In this retrospective study, we reported the G‐CSF use and risk of DIP in 234 DLBCL patients and 87 FL patients receiving R‐CHOP‐type immunochemotherapy. Results In 72% of patients, the treatment included a G‐CSF support. The overall incidence of treatment‐induced pneumonitis was 6.9% in this patient group. All the DIP cases (n = 16) were among patients receiving G‐CSF support (p = 0.03). Older age (over 60 years) and higher disease stage (Ann Arbor 3–4) also increased the risk of DIP. Conclusions These findings suggest that the use of G‐CSF increases the risk of DIP, when used in combination with rituximab‐containing regimen.